Vitamin D deficiency and its correlation with pregnancy outcome - Menon, Maya; A., Sridevi T.; Mohan, Thuthi; Patil, Aruna B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: There is a growing concern about the high prevalence of vitamin D deficiency and its relationship with variety of diseases worldwide. The objective of this study was to determine the prevalence of vitamin D deficiency and its association with pregnancy outcome. Methods: This was a cross sectional study conducted among 150 antenatal women from October 2014 to April 2015. Data containing socio-demographic details, vitamin D level, serum calcium, pregnancy complications and growth situation of newborns were collected and analyzed. Results: A total 150 pregnant women participated in the study, 75.3% were vitamin D deficient, 22.1% vitamin D insufficient and 2.6% normal. There was no significant adverse maternal outcome. NICU admission was required in 28.3 and 15.2% in the vitamin D deficient and insufficient groups respectively. Conclusions: Women from different socioeconomic status, irrespective of parity and educational levels had vitamin D deficiency and insufficiency. This study fails to show a relation of vitamin D deficiency with other high-risk factors of pregnancy and does not show any adverse fetal outcome.